Composition of dissolved organic matter controls interactions with La and Al ions: Implications for phosphorus immobilization in eutrophic lakes. (May 2019) - Du, Yingxun; Zhang, Qiaoying; Liu, Zhengwen; He, Hu; Lürling, Miquel; Chen, Musong; Zhang, Yunlin
Abstract: Applications of aluminium (Al) salt or lanthanum (La) modified bentonite (LMB) have become popular methodologies for immobilizing phosphorus (P) in eutrophic lakes. The presence of humic substances, has been shown to inhibit this form of treatment due to the complexation with La/Al. However, the effects of other dissolved organic matter (DOM), especially that derived from phytoplankton (the dominant source in eutrophic lakes) are unknown. In this study, the interaction with La/Al of Suwannee River Standard Humic Acid Standard II (SRHA) and algae-derived DOM (ADOM) were investigated and compared. Differed to SRHA which was dominated by polyphenol-like component (76.8%, C1-SRHA), majority in ADOM were protein-like substance, including 41.9% tryptophan-like component (C2-ADOM) and 21.0% tyrosine-like component (C3-ADOM). Two reactions of complexation and coprecipitation were observed between SRHA/ADOM and La/Al. Complexation dominated at low metal inputs less than 10 μM and coprecipitation was the main reaction at higher metal inputs. For ADOM, the tryptophan-like component (C2-ADOM) was the important component to react with metal. The reaction rate for C2-ADOM with La were about two-third of that for C1-SRHA, indicating that the influence of C2-ADOM was significant during the P immobilization by La/Al-based treatment in eutrophic lakes. The P removal data in the presence of ADOM confirmed the significant inhibition of ADOM. In addition, based on the composition of coprecipitates and relatively biodegradable character of tryptophan-like substances (C2-ADOM), the coprecipitation of ADOM was assumed to reduce the stability of precipitated P in eutrophic lakes. The release of P from the potential biodegradation of the coprecipitates and thus the possible decline of the performance of P immobilization by La/Al-based treatments is an important work in the future. Graphical abstract: Image 1 Highlights: Complexation and coprecipitation occurred between SRHA/ADOM and La/Al. A tryptophan-like component of ADOM complexed strongly with La. The tryptophan-like component has strong ability to coprecipitate with La and Al. The behaviors of PARAFAC components explained the inhibitory effect of SRHA/ADOM on P removal. The stability of coprecipitates of DOM, Al/La and P should be noted.